Synergism of Wild Grass and Hydrocarbonoclastic Bacteria in Petroleum Biodegradation - Gofar, Nuni (UNIVERSITY OF LAMPUNG, 2013)
The concept of plants and microbes utilization for remediation measure of pollutant contaminated soil is the newest development in term of petroleum waste management technique. The research objective was to obtain wild grass types and hydrocarbonoclastic bacteria which are capable to synergize in decreasing petroleum concentration within petroleum contaminated soil. This research was conducted by using randomized completely block design. This research was conducted by using randomized completely block design. The first factor treatments were consisted of without plant, Tridax procumbens grass and Lepironia mucronata grass. The second factor treatments were consisted of without bacterium, single bacterium of Alcaligenes faecalis, single bacterium of Pseudomonas alcaligenes, and mixed bacteria of Alcaligenes faecalis with P. alcaligenes. The results showed that mixed bacteria (A. faecalis and P. alcaligenes) were capable to increase the crown and roots dry weights of these two grasses, bacteria population, percentage of TPH (total petroleum hydrocarbon) decrease as well as TPH decrease and better pH value than that of single bacterium. The highest TPH decrease with magnitude of 70.1% was obtained on treatment of L. mucronata grass in combination with mixed bacteria.[How to Cite: Gofar N. 2013.Synergism of Wild Grass and Hydrocarbonoclastic Bacteria in Petroleum Biodegradation. J Trop Soils 18 (2): 161-168. Doi: 10.5400/jts.2013.18.2.161][Permalink/DOI: www.dx.doi.org/10.5400/jts.2013.18.2.161]REFERENCESBello YM. 2007. Biodegradation of Lagoma crude oil using pig dung. Afr J Biotechnol 6: 2821-2825.Gerhardt KE, XD Huang, BR Glick and BM Greenberg. 2009. Phytoremediation and rhizoremediation of organic soil contaminants: Potential and challenges. Plant Sci 176: 20-30.Glick BR. 2010. Using soil bacteria to facilitate phytoremediation. Biotechnol Adv 28: 367-374. Gofar N. 2011. Characterization of petroleum hydrocarbon decomposing fungi isolated from mangrove rhizosphere. J Trop Soils 16(1): 39-45. doi: 10.5400/jts.2011.16.1.39Gofar N. 2012. Aplikasi isolat bakteri hidrokarbonoklastik asal rhizosfer mangrove pada tanah tercemar minyak bumi. J Lahan Suboptimal 1: 123-129 (in Indonesian). Hong WF, IJ Farmayan, CY Dortch, SK Chiang and JL Schnoor. 2001. Environ Sci Technol 35: 1231.Khashayar T and T Mahsa. 2010. Biodegradation potential of petroleum hydrocarbons by bacterial diversity in soil. Morld App Sci J 8: 750-755.Lal B and S Khanna. 1996. Degradation of Crude Oil by Acinetobacter calcoaceticus and Alcaligenes odorans, J Appl Bacteriol 81: 355- 362.Mackova M, D Dowling and T Macek. 2006. Phytoremediation and rhizoremediation: Theoretical background. Springer, Dordrecht, Netherlands. 300 p. Malik ZA and S Ahmed. 2012. Degradation of petroleum hydrocarbons by oil field isolated bacterial consortium. Afr J Biotechnol 11: 650-658.Mendez MO and RM Maier. 2008. Phytostabilization of mine tailings in arid and semiarid environment an emerging remediation technology. Environ Health Prospect 116: 278-283.Milic JS, VP Beskoski, MV Ilic, SM Ali, GDJ Cvijovic and MM Vrvic. 2009. Bioremediation of soil heavily contaminated with crude oil and its products: composition of the microbial consortium. J Serb Chem Soc 74: 455-460.Mukre AM, AA Hamid, A Hamzah and WM Yusoff. 2008. Development of three bacteria consortium for the bioremediation of crude petroleum-oil in contaminated water. J Biol Sci 8: 73-79.Ndimele PE. 2010. A review on the phytioremediation of petroleum hydrocarbon. Pakistan J Biol Sci 12: 715-722.Newman LA and CM Reynolds. 2004. Phytoremediation of organic compounds. Curr Opin Biotechnol 15: 225-230.Onwuka F, N Nwachoko, and E Anosike. 2012. Determination of total petroleum hydrocarbon (TPH) and some cations (Na+, Ca2+ and Mg2+) in a crude oil polluted soil and possible phytoremediation by Cynodon dactylon L (Bermuda grass). J Environ Earth Sci 2: 12-17.Pezeshki SR, MW Hester, Q Lin and JA Nyman. 2000. The effect of oil spill and clean-up on dominant US Gulf Coast Marsh Macrophytes: a review. Environ Pollution 108: 129-139.Pikoli MR, P Aditiawati and DI Astuti. 2000. Isolasi bertahap dan identifikasi isolat bakteri termofilik pendegradasi minyak bumi dari sumur bangko. Laporan Penelitian pada Jurusan Biologi, ITB, Bandung (unpublished, in Indonesian).Pilon-Smits E and JL Freeman. 2006. Environmental cleanup using plants: biotechnological advances and ecological considerations. Front Ecol Environ 4: 203-10. Rahman KSM, JT Rahman, P Lakshmanaperumalsamy, and IM Banat. 2002. Towards efficient crude oil degradation by a mixed bacterial consortium. Bioresource Technol 85: 257-261.Rossiana N. 2004. Oily Sludge Bioremediation with Zeolite and Microorganism and It’s Test with Albizia Plant (Paraserianthes falcataria) L (Nielsen). Laboratory of Environmental Microbiology, Department of Biology Padjadjaran University, Bandung (unpublished).Rossiana, N. 2005. Penurunan Kandungan Logam Berat dan Pertumbuhan Tanaman Sengon (Paraserianthes falcataria L (Nielsen) Bermikoriza dalam Media Limbah Lumpur Minyak Hasil Ekstraksi. Laboratorium Mikrobiologi dan Biologi Lingkungan Jurusan Biologi Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Padjajaran, Bandung (in Indonesian).Sathishkumar M, B Arthur Raj, B Sang-Ho, and Y Sei-Eok. 2008. Biodegradation of crude oil by individual bacterial strains and a mixed bacterial consortium isolated from hydrocarbon contaminated areas clean. Ind J Biotechnol 36: 92-96.Shirdam R, AD Zand, GN Bidhendi and N Mehrdadi. 2008. Phytoremediation of hydrocarbon-contaminated soils with emphasis on effect of petroleum hydrocarbons on the growth of plant species. Phytoprotection 89: 21-29.Singer AC, DE Crowley and IP Thompson. 2003. Secondary plant metabolites in phytoremediation and biotransformation. Trends Biotechnol 21: 123-130.Singh A and OP Ward. 2004. Applied Bioremediation and Phytoremediation. Springler, Berlin, 281p.Surtikanti H and W Surakusumah. 2004. Peranan Tanaman dalam Proses Bioremediasi Oli Bekas dalam Tanah Tercemar. Ekol Biodivers Trop 2: 48-52 (in Indonesian).Wenzel WW. 2009. Rhizosphere processes and management in plant-assisted bioremediation (phytoremediation) of soil. Plant Soil 321: 385-408.Widjajanti H, I Anas, N Gofar and MR Ridho. 2010. Screening of petroleum hydrocarbons degrading bacteria as a bioremediating agents from mangrove areas. Proceeding of International Seminar, workshop on integrated lowland development and management, pp. C7 1-9.Widjajanti H. 2012. Bioremediasi Minyak Bumi Menggunakan Bakteri dan Kapang Hidrokarbonoklastik dari Kawasan Mangrove Tercemar Minyak Bumi. [Disertasi]. Universitas Sriwijaya (in Indonesian).